Quick Trust and Slow Time: Relational Innovations in Disability Performing Arts Practice. (28th June 2022) - Hadley, Bree; Paterson, Eddie; Little, Madeleine
Abstract : In the last decade, the field of Disability Arts has been recognised as a powerful source of aesthetic innovation. Yinka Shonibare has described it as 'the last remaining avant-garde movement' (Bragg, 2007), where artists with lived experience of disability produce new combinations of form, content and politics, which engage spectators in provocative reflections on the way we relate to each other in the public sphere. Despite a range of policies, plans, protocols and funding programmes to support disabled artists and collaborations between mainstream producers and disabled artists, the statistics – at least in our context in Australia – suggest most disability art still occurs outside and alongside an industry that struggles to include these artists. In this article, we draw upon findings from a series of workshops with disabled artists around Australia, conducted as part of the ARC funded Disability in the Performing Arts in Australia: Beyond The Social Model project – known colloquially to its collaborators and participants as 'The Last Avant Garde' project (https://lastavantgarde.com.au ) – to propose a new approach. We find that while provision of logistical access (ramps, hearing loops, interpreters) and ideological access (stories, characters, discourse and language) is critical, so is methodological access, which embodies disability culture in training, rehearsal and production processes. Disabled artists use crip culture, along with relational space and time to negotiate what happens in disability arts and culture production practices and work through desire, fear, vulnerability and reciprocity to rapidly establish trusting collaborations. It is inclusion of disability culture relationships and concepts, as much as ramps and inclusive language, that makes a practice feel safe for disabled artists – and this, we argue, is what the mainstream sector has to learn and what the disability arts sector has to teach about improving the inclusivity of the creative industries.